Expression of Concern. Relationship between body mass index and oral health indicators: a cross-sectional study - The Publisher (PAGEPress Publications, 2023)
This is a note of a temporary expression of concern related to the above-mentioned publication, as an occurrence of duplicate publication has been discovered. The Authors, their Institutions and other entities are investigating the issue of possible misconduct by a third entity. Evidence of inappropriate dual publication is available and will remain confidential while the investigation is ongoing; due to various complexities, the investigation will not be complete for a considerable time. The concern and this note will remain appended to the above-mentioned article, unless the parties provide the editors of the journal and the Publisher with a solution to the dispute.   Reference Niakan Lahiji M, Moghaddam OM, Ameri F, Pournajafian A, Mirhosseini F. Relationship of vitamin D level with insulin dosage required based on insulin therapy protocol. Eur J Transl Myol 2023 Feb. 3; https://doi.org/10.4081/ejtm.2023.11017